An All‐Inclusive and Straightway Laboratory Activity to Solve the Three‐Dimensional Crystal Structure of a Protein. Issue 6 (24th August 2019) - Klinke, Sebastián; Rinaldi, Jimena; Goldbaum, Fernando A.; Suarez, Sebastián; Otero, Lisandro H.
Abstract: X‐ray crystallography provides structural information of molecules at the atomic level, being a central technique at the forefront of science and technology. However, crystallography teaching is not usually implemented in biochemistry lab classes due to its complex execution by nonexpert users. Here, we report the basic step‐by‐step workflow performed by crystallographers in order to solve the three‐dimensional structure of a protein. All these activities were executed in a course for Latin‐American graduate students with no previous knowledge on X‐ray crystallography entitled "Crystallography in Structural Biology: why do we need a protein crystal, and how do we get it?." We would like to share our experience with the educational research community, with the main purpose being to enrich teaching in biochemistry and structural molecular biology by performing a series of interesting laboratory and computer experiments. © 2019 International Union of Biochemistry and Molecular Biology, 47(6):700–707, 2019.